Penerapan Media Digital Dalam Meningkatkan Aktivitas Siswa Pada Pembelajaran PAI di Kelas IV SD Negeri 06 Pauh Lubuk Sikaping - Yermaida, Adila (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to investigate the influence of social media use on students’ academic achievement. This research used a quantitative design with a survey method. The research sample was high school students in [Your City]. Data was collected through questionnaires distributed to students. The results showed that there was a significant relationship between the frequency of social media use and students’ academic achievement. Students who frequently use social media for learning purposes tend to have better academic achievement compared to students who rarely use social media for learning purposes. However, excessive use of social media can have a negative impact on academic achievement. This study concludes that the effective use of social media can be a useful tool to improve students’ academic achievement.